Swot Analysis to Determine a Company's Strategy in the State of the Covid -19 Plaguein XYZ Company - Safa’at; Nuzulul Fatimah; Ahmad, Muhammad Ali (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2021)
PT. XYZ is a company engaged in the field of readymix concrete. This study aims to determine the company's strategy in a covid-19 epidemic state, it is hoped that the company will be able to deal with it well. The method used is by interviewing employees in accordance with their fields and collecting the necessary documents, from the data are evaluated and then the strategy is prepared. From the results of the study concluded that with the SWOT analysis the company's position is located in quadrant 4.